Effects of land use systems on total organic carbon and carbon in the oxidizable fractions of soil organic matter - Simone Cândido Ensinas Maekawa; Luana Larissa de Souza; Giovanna Stephanie Beluque Gonçalves; Diego Menani Heid (Agro@mbiente On-line)
Adopting conservationist land use systems can contribute to soil carbon storage and minimize climate change. Given the above, the research aimed to quantify and compare the contents of total organic carbon (TOC) and oxidizable fractions of soil organic matter (SOM) in different land use systems. The research was conducted in soils classified as Latossolo Vermelho Distroférrico; soil samples were collected in the 0-0.10, 0.10-0.20, and -0.20-0.30 m soil layers. The treatments consisted of five land use systems (soybean/corn succession in a no-till system, cassava in conventional tillage, eucalyptus, permanent pasture, and reformed pasture) plus a reference area (native cerrado vegetation). The adoption of the no-till system was efficient in promoting greater increases in TOC contents, on the other hand, conventional tillage presented the lowest TOC contents throughout the soil profile (0-30 cm) studied. No-till system promoted the best benefits in increasing carbon in the F1 (labile), F2 (moderately labile), and F3 (recalcitrant) fractions of SOM. Determining carbon in the oxidizable fractions of SOM proved sensitive for evaluating changes caused by land use systems. Adopting the no-till system contributes consistently to increasing TOC contents, helping to mitigate greenhouse gas emissions and promoting improved soil quality.